7q11.23 deletion and duplication. (June 2021) - Osborne, Lucy R; Mervis, Carolyn B
Abstract : Copy number variation (CNV) at 7q11.23 causes distinct disorders with both contrasting and overlapping phenotypic features of some but not all of the genes encompassed by the CNV. The spectrum of cognitive disabilities, psychopathology and altered behaviours associated with 7q11.23 CNV provides a tantalizing window of opportunity to better understand the molecular bases for complex human cognitive function and social behaviour. Study of individuals with atypical CNVs has narrowed the field of candidate genes, and the generation of mouse models has allowed further insight into their functions. Recent research has used high-throughput genomics techniques to interrogate the transcriptome and methylome, and initial strategies to correct gene transcription levels, pathophysiology and cognitive and behavioural phenotypes show promise.